Delay in decision and determinants for safe abortion among women at health facilities in south West Ethiopia: facility based cross sectional study - Biru Abdissa Mizana; Tsige Woyecha; Samuel Abdu (BMC, 2020)
Abstract Background Delayed safe abortion is the most common cause of gynecologic admission in developing countries. The study, therefore, assessed the delay decision for safe abortion and determinant factors among women at health facilities in South West Ethiopia. Methods Facility-based cross-sectional study was conducted among 384 women who were selected from health facilities by using simple random sampling. A pre-tested structured questionnaire was used for data collection. Data were entered into Epidata and exported to SPSS for analysis. Binary Logistic regression was used and Variables with P-value < 0.25 during bivariate analysis were included in the multivariable logistic regression model. Finally, variables with p-value ≤0.05 were judged as a statistically significant association. Results The magnitude of delay decision for safe abortion services was 70.8% (0.66, 075). Place of residence [AOR 2.44 (95% C.I: (1.39, 4.30)], lack of formal education [AOR: 2.41 (95% C.I:(1.08, 3.59)], level of education [AOR: 2.22 (95% C.I: (1.19, 4.11)], history of previous abortion [AOR: 3.47 (95% C.I: (1.74, 8.6.91)] and late confirmation of pregnancy [AOR: 1.64 (95% C.I: (1.01-2.65)] were the determinant factors for delay in decision for safe abortion. Conclusion This study revealed that the majority of women were delayed for the decision of safe abortion services. Place of residence of the women, lack of formal education, history of previous abortion and late confirmation of pregnancy were the determinant factors for women's decision for safe abortion. Therefore, it is better to work on awareness creation the timing of safe abortion and complication of delay abortion especially for the women from rural area.